CONVERGENCE IN PROVINCIAL‐LEVEL SOUTH AFRICAN HOUSE PRICES: EVIDENCE FROM THE CLUB CONVERGENCE AND CLUSTERING PROCEDURE. Issue 1 (24th February 2015) - Apergis, Nicholas; Simo‐Kengne, Beatrice D.; Gupta, Rangan
Abstract : This empirical study analyzes the long run behavior of provincial house prices in South Africa based on the club convergence and clustering procedure of Phillips and Sul. Using quarterly data covering the period of 1976Q2–2012Q4, 1974Q1–2012Q4 and 1977Q3–2012Q4 for the large, medium, and small middle segments of the housing market, respectively, we test the law of one price across nine provinces. The empirical findings suggest that the nine provinces do not form a homogeneous convergence club. Unlike the small middle segment, which consists of two convergence clubs of seven and two provinces, the large and medium middle segments have three convergence clubs corresponding to three segmented independent local markets. Possible intuitive explanations for the existence of such clubs are discussed and resulting policy implications provided.